Pemanfaatan Limbah Tandan Kelapa Sawit Sebagai Media Pertumbuhan Jamur Merang (Volvariella volvacea) - Prayoga, Shinta Regina; Novianti, Dewi; Mutiara, Dian (PPSDP Undergraduate Journal of Educational Sciences, 2025)
Research has been carried out on the use of oil palm bunch waste as a medium for the growth of merang mushrooms. Oil Palm Empty Bunches (TKKS) is waste from the processing of Fresh Fruit Bunches (FFB). The research will be carried out in April-May 2024. The purpose of the study was to analyze the use of empty oil palm bunch waste as a medium for the growth of merang mushrooms. The study used an experimental method in a complete randomized design (RAL) consisting of 5 treatments and 5 replicates. Observation parameters include harvest time (days) and wet weight (grams). The results of the study had a real effect on the harvest time and wet weight of merang mushrooms, the highest harvest time (the longest) was 12.80 days in the P1 treatment and the lowest (fastest) was 11.40 days in the P2 treatment and the highest wet weight (the most) was 240 grams in the P2 treatment and the lowest (least) was 70 grams in P1. Empty bunches of oil palm can be used as a medium for the growth of merang mushrooms.